Annual review of the sociology of religion - Cipriani, Roberto.; Garelli, Franco. (Annual Review of the Sociology of Religion, 2016)
Recent studies show that atheism is increasing. The reasons for this development have not as yet been examined thoroughly. Many atheists continue to be residual groups in surveys on religiosity, making it difficult to examine who they are and why they have chosen to be atheists. Moreover, they are minority groups in most countries (former Soviet bloc countries are left out of discussion); many do not identify with any organized groups of atheists or agnostics. Atheist groups and ideologies, then, represent a wide range of attitudes, behaviour and ways of acting towards religion. The lack of a clear definition of what being atheist (or an unbeliever) means today invites us to study the issue in greater depth. This volume represents a first attempt at understanding and scrutinizing atheism. Thanks to all contributors, it provides both a global perspective and specific insights into specific cases.